Reviewing the impact of 11 national Be Clear on Cancer public awareness campaigns, England, 2012 to 2016: A synthesis of published evaluation results. Issue 5 (7th November 2020) - Lai, Jennifer; Mak, Vivian; Bright, Chloe J.; Lyratzopoulos, Georgios; Elliss‐Brookes, Lucy; Gildea, Carolynn
Abstract: The Be Clear on Cancer (BCoC) campaigns have run in England since 2010. They aim to raise awareness of possible cancer symptoms, encouraging people to consult a general practice with these symptoms. Our study provides an overview of the impact of 11 national campaigns, for bowel, lung, bladder and kidney, breast and oesophago‐gastric cancers. We synthesised existing results for each campaign covering seven clinical metrics across the patient pathway from primary care attendances to one‐year net survival. For each metric, "before" and "after" periods were compared to assess change potentially related to the campaign. Results show that primary care attendances for campaign‐related symptoms increased for 9 of 10 campaigns and relevant urgent referrals for suspected cancer increased above general trends for 9 of 11 campaigns. Diagnostic tests increased for 6 of 11 campaigns. For 7 of 11 campaigns, there were increases in cancer diagnoses resulting from an urgent referral for suspected cancer. There were sustained periods where more cancers were diagnosed than expected for 8 of 10 campaigns, with higher than expected proportions diagnosed at an early stage for sustained periods for 4 of 10 campaigns. There was no impact on survival. In summary, there is evidence that the BCoC campaigns impact help‐seeking by patients and referral patterns by general practitioners, with some impact on diagnosis (incidence and stage). There was no clear evidence of impact on survival. Abstract : What's new? Starting in 2010, the "Be Clear on Cancer" public awareness campaigns in England have promoted awareness of possible cancer symptoms, encouraging people with these symptoms to seek help without delay. This study is the first to evaluate the impact of 11 national campaigns for bowel, lung, bladder and kidney, breast, and oesophago‐gastric cancers on multiple points of the patient pathway. Evidence shows that the campaigns influence help‐seeking by patients and primary care referral patterns, with some impact on diagnosis (incidence and stage) but no impact on survival. The findings have potential implications for the design and sequencing of future campaigns.